The Criteria of Evaluating the Ability to Speak for Children of Preschool Age - Cupere, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Human interaction is possible with the help of communication. With the communication activity realization we need to develop our communication competence. Narrative skills development level is human’s individual skill, consequently and coherently transmitting his thoughts, knowledge and experience for interlocutor choosing right language tools and grammatical construction. This skills child learns in preschool age and has to develop in throughout life.Speech disorders, particularly insufficient development of the language system, have important influence on narrative skills development. Further this problem could badly affect the communicative activity realization. For this problem minimization should be help to children to develop their narrative skills. Before starting corrective developing work for children with insufficient development of language system, it is required to assess child narrative skills development level. This is an analysis of children narrative skills development opportunity and practical recommendations.